Financial Planning - Planning for the Future - T S, Ramachandran (Ushus Journal of Business Management, 2005)
Planning is a process of bridging the gap between where you are and where you want to be. Financial planning is a process of setting financial objectives and having a road map to reach these objectives. It is planning for the future. Every individual is required to be clear about his financial objectives and the road map to reach the same, irrespective of his financial status and his age, for the simple reason that it is better to have one, than not having one. The necessity of money in one's life and the security, both physiological and psychological, that money provides cannot be underplayed. Given this, the article proceeds to describe various financial stages of a common man and provides a broad sketch of how one can achieve his financial objectives, given the space limitations.